1994
DOI: 10.1121/1.408683
|View full text |Cite
|
Sign up to set email alerts
|

A perceptual study of source coding of Fourier phase and amplitude of the linear predictive coding residual of vowel sounds

Abstract: A practical question in a Fourier transform coding of speech signals is to what accuracy their amplitude and phase spectra have to be represented without perceptible distortions. In this paper a concern is with the audibility of quantization noise signals which are produced by quantizing the amplitude and phase spectra of vowel sounds. Experiments show that the detection of the noise targets with maskers of a low fundamental frequency is determined mainly by the sharpest temporal resolution of the auditory sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…We have identified that the residual Fourier phase contributes significantly to preserving naturalness in the synthesized noises. This agrees with the conclusion reported in [12] that the phase spectrum of the LP residual determines the temporal waveform and contributes significantly to the overall quality.…”
Section: Spectral Excitation Modelsupporting
confidence: 93%
“…We have identified that the residual Fourier phase contributes significantly to preserving naturalness in the synthesized noises. This agrees with the conclusion reported in [12] that the phase spectrum of the LP residual determines the temporal waveform and contributes significantly to the overall quality.…”
Section: Spectral Excitation Modelsupporting
confidence: 93%
“…We have identified that the residual Fourier phase contributes significantly to preserving naturalness in the synthesized noises. This agrees with the conclusion reported in [9] that the phase spectrum of the LP residual determines the temporal waveform and contributes significantly to the overall quality. Direct coding of residual phase is not possible with the very low-bit rate constraint.…”
Section: Linear Prediction-based Noise Codingsupporting
confidence: 93%